2000
DOI: 10.1029/2000gl000054
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of parallel current at substorm breakup

Abstract: Abstract. We study the development of substorm breakups characterized by dispersionless injections of energetic particles at the geostationary orbit. The corresponding magnetic signature is a fast change from tail-like to dipolelike configuration with transient superimposed low frequency oscillations (T~I mn). We show that intense waves (fib --1 nT) with shorter periods (1 s) systematically develop at breakup, and that their intensification is strongly related to the dipolarization and to the fast increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
(2 reference statements)
0
17
0
Order By: Relevance
“…Further analysis of GEOS-2 data (at the geostationary orbit) suggested that substorm onset and impulsive plasma transport is controlled by a micro-instability with frequencies around the proton gyrofrequency such as a parallel current instability (Perraut et al 2000a(Perraut et al , 2000bLe Contel et al 2001a, 2001b. The regular occurrence at different radial distances (at the geostationary orbit with GEOS-2, at 10 R E with Geotail and 20 R E with Cluster) of wave activity around the proton gyrofrequency at substorm onset was also noted by Le Contel et al (2002).…”
Section: Introductionmentioning
confidence: 98%
“…Further analysis of GEOS-2 data (at the geostationary orbit) suggested that substorm onset and impulsive plasma transport is controlled by a micro-instability with frequencies around the proton gyrofrequency such as a parallel current instability (Perraut et al 2000a(Perraut et al , 2000bLe Contel et al 2001a, 2001b. The regular occurrence at different radial distances (at the geostationary orbit with GEOS-2, at 10 R E with Geotail and 20 R E with Cluster) of wave activity around the proton gyrofrequency at substorm onset was also noted by Le Contel et al (2002).…”
Section: Introductionmentioning
confidence: 98%
“…Wave activation is often observed at substorms. At the geostationary orbit, small‐scale Alfvénic fluctuations are systematically observed at substorm onset and during the expansion phase [ Perraut et al , 2000b]. As shown by Le Contel et al [2001b], plasma transport can be controlled by the amplitude of these waves.…”
Section: Introductionmentioning
confidence: 99%
“…Impulsive increases (as short lasting bursts) of these waves were regularly observed at the GEOS 2 during the substorm magnetic field dipolarization (Perraut et al, 1993(Perraut et al, , 2000Le Contel et al, 2001). These spatially localized waves are related to field-aligned currents, Perraut et al (2000) called them the current-driven Alfvén (CDA) waves.…”
Section: Oscillations Associated With a Sharp Front Of Energetic Ionsmentioning
confidence: 99%
“…These spatially localized waves are related to field-aligned currents, Perraut et al (2000) called them the current-driven Alfvén (CDA) waves. Bursts of CDA waves coincide with the increases in the flux of electrons with energy >20 keV at pitch-angles ∼90 • and, simultaneously, with the increases of low-energy (2.5-7 keV) electron fluxes at pitch-angles <20 • (Perraut et al, 1993(Perraut et al, , 2000. Also, the high-intensity CDA waves may isotropize and heat the ions (Perraut et al, 1998).…”
Section: Oscillations Associated With a Sharp Front Of Energetic Ionsmentioning
confidence: 99%